Genetic Diversity studies in Elite Rice Landraces of North-Western Himalayas - Thakur, Ananya; Kumar, Naresh V; Bhardwaj, Neelam (Journal of Cereal Research, 2023)
Forty elite rice landraces were evaluated for their morphological diversity by raising in Randomized Complete Block Design withthree replications during kharif, 2022. Data was recorded for yield and its contributing traits viz., days to 50% flowering, days to 75%maturity, plant height, panicle length, total tillers per plant, spikelet per panicle , grains per panicle , grain yield per plant and grainyield per plot. Among all the traits under study, 1000 grain weight was found to be maximum contributing trait towards divergencefollowed by grain yield per plant. All the 40 genotypes were divided into 7 distinct clusters in accordance on the basis of morphologicaldata. Out of these, Cluster I consisted of the highest number of genotypes (29 genotypes) while with 5 genotypes, Cluster II hasbeen found to have the largest intra-cluster distance. The highest inter-cluster distance was observed between Cluster VI and ClusterVII, suggesting the possibility of generating segregating populations, if parents are chosen for a hybridization programme from theseclusters.